Analysis of Water Characteristics, Leptospira Bacteria, and Environmental Factors in the Leptospirosis Cases in Boyolali Regency - Cornelia Palmasari Ariesta Putri; Lintang Dian Saraswati; Mateus Sakundarno Adi; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Leptospirosis is a direct zoonosis whose transmission related to environmental and behavioral factors. Boyolali is a Leptospirosis endemic area in Central Java with a high number of cases and CFR. In 2017, Leptospirosis cases in Boyolali Regency reached 40.62 per 100,000 populations (CFR = 23.52%). The study aims to analyze the water characteristics, Leptospira bacteria, and environmental factors and risk behavior in Leptospirosis cases in Boyolali Regency. This study used observational method with a case control approach. The population in this study were Leptospirosis cases in Boyolali Regency with a sample of 34 cases and 34 controls, and also 62 water samples. The results of this study showed that water samples had an optimal temperature and pH, but Leptospira bacteria were not found in all water samples. This study also showed that there was a relationship between the presence of garbage in the house (p=0.039; OR=2,133) and presence of pets (p=0.011; OR=0,150) with the incidence of Leptospirosis in Boyolali Regency. The conclusion of this study is that Leptospira bacteria were not found in all water samples, and the environmental factors that related to the incidence of Leptospirosis in Boyolali Regency are the presence of garbage in the house and the presence of pets.Leptospirosis is a direct zoonosis whose transmission related to environmental and behavioral factors. Boyolali is a Leptospirosis endemic area in Central Java with a high number of cases and CFR. In 2017, Leptospirosis cases in Boyolali Regency reached 40.62 per 100,000 populations (CFR = 23.52%). The study aims to analyze the water characteristics, Leptospira bacteria, and environmental factors and risk behavior in Leptospirosis cases in Boyolali Regency. This study used observational method with a case control approach. The population in this study were Leptospirosis cases in Boyolali Regency with a sample of 34 cases and 34 controls, and also 62 water samples. The results of this study showed that water samples had an optimal temperature and pH, but Leptospira bacteria were not found in all water samples. This study also showed that there was a relationship between the presence of garbage in the house (p=0.039; OR=2,133) and presence of pets (p=0.011; OR=0,150) with the incidence of Leptospirosis in Boyolali Regency. The conclusion of this study is that Leptospira bacteria were not found in all water samples, and the environmental factors that related to the incidence of Leptospirosis in Boyolali Regency are the presence of garbage in the house and the presence of pets.